HYBRIDVENTURI-ORIFICE MICROBUBBLE GENERATOR FOR OXYGEN DISSOLUTION IN WATER - LIEW CHUNG , KELLY SHI (2020)
Microbubbles with slow rising speedandhigher specific area are excellent in promoting greater oxygen dissolution rate in water. Such attributes are very important to tackle challenges on the low efficiency of gas/liquid mass transfer that occurs in aerobic wastewater treatment systems or in the aquaculture industries. Microbubble-type aerator had succeeded in enhancing the growth rate of fish and oyster, purifying the fishery waste water. Various approaches havebeen implemented to increase the aeration efficiency ofthe microbubble generator (MBG). However, current literature mostly cover fundamental mechanism of microbubble generation and characteristics instead of directly evaluating the oxygen transfer efficiency.In this study, the performanc eand energy efficiency of a hybrid venturi-orifice based MBG were investigated. The experiments were run under three conditions: various liquid velocity (QL)at fixed Qg; various Qg of at fixed QL; and free flowing air at variable QLs. Under free-flowing air, it is reaching a plateau KLavalue of 0.040min-1withaeration efficiency of0.429kgO2/kWh. The findings reveal that the hybrid venturi-orifice MBGis functioning as aerator for water. However, it can be further optimized for greater efficiency.